COMPARATIVE CHARACTERIZATION OF SOME FUNCTIONAL PROPERTIES OF FLOURS OF NEW PLANTAIN HYBRIDS WITH THE ORISHELE VARIETY (MUSA SPP.) AS CONTROL - Coulibaly, Souleymane; Tetchi, Achille F.; Adou, Marc; Amani, Georges N. (Emirates Journal of Food and Agriculture, 2012)
Plantain hybrids CRBP 14, CRBP 39, FHIA 17 and FHIA 21 gives higher yields than traditional ones and have been conceived in response to the increasing plantain demand. The capability of these new hybrids to replace the traditional varieties was shown by the study of some functional characteristics of their native flours, in comparison with that of Orishele variety as control. Swelling power and solubility patterns of flours evolve in a homogeneous way for all cultivars, with however a particularity for hybrid FHIA 17, for which these phenomena occur earlier. This hybrid shows the lowest swelling values of its flour. Viscoamylograms indicate an earlier initial temperature of gelatinization (26th min at 74°C) for hybrids CRBP 14, FHIA 17 and FHIA 21 than for hybrid CRBP 39 and the control variety Orishele (30th min at 77°C). Hybrid FHIA 17 presents the highest values for viscosities at 95°C and at 50°C, as for the indices of gelation and instability. Plantain hybrids CRBP 14, CRBP 39 and FHIA 21 being characterized by technological aptitudes close to those of the control variety Orishele, they can thus replace it. Hybrid FHIA 17 would be a dessert type banana.